Budaya Keselamatan Pasien di Private Hospital - Santoso, Budi; Wiyadi, Wiyadi; Romadhon, Yusuf Alam; Imronudin, Imronudin (Journal of Telenursing (JOTING), 2024)
This study aims to analyze patient safety culture and identify the strengths and weaknesses that influence the perception of this culture in a private hospital. The research method uses a cross-sectional descriptive study approach. The results of the study indicate that efficient teamwork, organizational learning in continuous improvement, and management support are the main strengths in safety culture. Response to errors in the moderate category is identified as a weakness. In conclusion, optimizing the improvement of safety culture can be achieved through identifying areas of improvement. Loss of information can be reduced with support for health worker feedback, reducing punitive actions, and developing standard tools Keywords: AHRQ, Safety Culture, Patient Cafety, Hospital